Chlorate and Other Oxychlorine Contaminants Within the Dairy Supply Chain. Issue 6 (10th October 2018) - McCarthy, William P.; O'Callaghan, Tom F.; Danahar, Martin; Gleeson, David; O'Connor, Christine; Fenelon, Mark A.; Tobin, John T.
Abstract: The presence of chlorate in milk and dairy products can arise from the use of chlorinated water and chlorinated detergents for cleaning and sanitation of process equipment at both farm and food processor level. Chlorate and other oxychlorine species have been associated with inhibition of iodine uptake in humans and the formation of methemoglobin, with infants and young children being a high‐risk demographic. This comprehensive review of chlorate and chlorine derivatives in dairy, highlights areas of concern relative to the origin and/or introduction of chlorate within the dairy supply chain. This review also discusses the associated health concerns, regulations, and chemical behavior of chlorate and chlorine‐derived by‐products, and provides a summary of mechanisms for their detection and removal.